Quantification of Soil Organic Carbon Stocks in the Mangrove Forest of Telaga Tujuh Island, Langsa, Aceh - Ashabul Anhar; Lola Adres Yanti; Ilham Hidayat; Ali Makmur; Arif Habibal Umam; Ilham Hanafi; Ariz Umar Ramadhan (Journal of Sylva Indonesiana, 2026)
Mangrove ecosystems are considered highly effective carbon sinks because of their substantial capacity to caputure and store carbon, especially in the form of soil organic carbon. This study aims to quantify the soil organic carbon stock in the mangrove forest of Telaga Tujuh Island, Langsa, using purposive sampling with eight circular plots of 400 m² each. Results showed that the diameter class distribution was dominated by the 10-20cm with 158 individuals. The tree density in this place was 796.88 ind. ha-1. The highest soil organic carbon stock was recorded in Plot 8, with a value of 811.24 Mg C ha-1. The mean of soil organic carbon stock was 635.28 ± 110.46 Mg C ha-1. Overall, the total soil organic carbon stock of Telaga Tujuh Island was estimated at 22,234.86 ± 3,866.20 Mg C ha-1. These results highlight the significant role of Telaga Tujuh mangroves as a carbon sink and their contribution to national carbon emission mitigation strategies.